Efforts to improve candle attitude movements in floor gymnastics learning using wall media - Rifki, Ahmad Yuski Maulana; WAHYUNI, Dewi (Jurnal Ilmu Keolahragaan, 2023)
This research aims to improve students' ability to perform candle attitude movements in floor gymnastics learning through the use of wall media as a learning tool. Candle stance movements are often a challenge for elementary school students because they demand proper strength, balance, and technique. This study uses a qualitative approach with the subjects of grade V students of SDN Sigentong 03, Wanasari District, Brebes Regency. Data was collected through observation during learning, interviews with PJOK teachers and students, and documentation of learning activities. The analysis technique used is qualitative descriptive analysis consisting of data reduction, data presentation, and conclusion drawn. The results of the study show that the use of wall media can help students understand and practice candle attitude movements more easily and safely. Students become more confident in making movements because of the physical assistance from the wall that supports the balance of the body. In addition, student involvement and motivation in attending lessons also increased significantly. PJOK teachers stated that this method is effective and can be an alternative in the floor gymnastics learning process. The conclusion of this study is that wall media is an effective tool in improving candle attitude movement skills in elementary school students. Teachers are advised to use school environment facilities as creative and contextual learning media.